Praia Grande of Príncipe Island (Gulf of Guinea): an important nesting beach for the green turtle Chelonia mydas - Loureiro, Nuno de Santos (2011)
The beach Praia Grande, on Príncipe Island (Gulf of Guinea, West Africa), hosts a green turtle rookery. A total of 219 clutches with an average size of 111 eggs were laid by the 88 females that nested there during the 2007-2008 nesting season. During the nesting season 2009-2010, 315 clutches, averaging 104 eggs, were laid by the 112 females that were recorded. During both seasons, nesting began in early September and lasted until late February, with a peak in December-January. In the 2009-2010 nesting season, the clutch frequency was 2.7 (SD = 1.3) and the average renesting interval 12.3 days (SD = 1.8). The average incubation duration of the clutches that were incubated in situ, shaded by the existing natural vegetation, was 60.4 days (SD = 1.4) However, throughout the 2007-2008 nesting season almost all the clutches were incubated in an unshaded hatchery and the average incubation duration was 3.2 days shorter. The data published here is the first report concerning the green turtle rookery on Praia Grande, Príncipe Island.